Phenomenology of Suicide Unlocking the Suicidal Mind (Springer International Publishing, 2018)
This book will help the reader to understand the suicidal mind from a phenomenological point of view, shedding light on the feelings of suicidal individuals and also those of clinicians. In accordance with the importance that the phenomenological approach attaches to subjectivity and sense of self as the starting points for knowledge, emphasis is placed on the need for the clinician to focus on the subjective experiences of the at-risk individual, to set aside prior assumptions, judgments, or interpretations, and to identify ways of bridging gaps in communication associated with negative emotions. The vital importance of empathy is stressed, drawing attention to the insights offered by neuroimaging studies and the role of mirror neurons in social cognition. It is widely acknowledged that when a clinician meets a person who wants to die by suicide, the clinician does not fully understand what is going on inside the mind of that individual. This book recognizes that any approach to suicide prevention must promote understanding of suicidal thoughts and feelings. The awareness that it fosters and the innovative perspectives that it presents will appeal to a wide readership.